Analisis Penerapan Model Problem Based Learning Terhadap Kemampuan Berpikir Spasial Pada Materi Sistem Informasi Geografis - Trully Yessyca Bana; Arfita Rahmawati; Erry Ersani (Universitas Negeri Gorontalo, 2025)
Spatial thinking ability is a core skill that students must possess to understand and solve problems in geography. Spatial thinking involves the integration of spatial concepts, spatial information methods, and reasoning processes that enable students to analyze spatial relationships. This cognitive skill allows learners to transform and collaborate between spatial concepts and representational tools to comprehend geospheric phenomena. This study aims to examine the implementation and influence of the Problem-Based Learning (PBL) model on improving students’ spatial thinking ability at SMA Negeri 1Amarasi Barat in the 2025/2026 academic year. The study employs a classroom action research design with a quantitative approach. The research subjects were students of classes X1 and X2. The research procedure consisted of planning, implementation, observation, data analysis, reflection, and follow-up stages. Data were collected through questionnaires and learning achievement tests, then analyzed using mean calculations and simple linear regression tests assisted by SPSS. The findings show a significant improvement in the experimental class, with the N-gain increasing from a pretest mean of 46.65 to a posttest mean of 71.57, while the control class decreased from 57.65 to 42.26. The hypothesis test revealed significance values (2-tailed) of 0.000 and 0.001 0.05, indicating that the PBL model has a significant positive effect on students’ learning outcomes. Thus, Problem-Based Learning is proven effective in enhancing spatial thinking and improving the quality of geography learning.